Is Seeing Intriguing? Practitioner Perceptions of Research Documents. Issue 1 (22nd January 2016) - Huber, Amy
ABSTRACT: Although design practitioners have a myriad of information sources available, they often have little time to evaluate the information. The need to study visual persuasive tactics is highlighted by (1) the propensity of designers to use visual communications, (2) the availability of sources that range in validity, (3) work stressors encountered by designers, and (4) the benefits of using peer‐reviewed sources. Given these contexts, it may behoove design scholars to acknowledge the constraints and desires of their intended audience, which may include practicing interior designers. Framed by Petty and Cacioppo's Elaboration Likelihood Model (ELM) of persuasion, this study's goal was to compare design practitioners' hedonic perceptions of empirical research documents. Thirty‐four participants completed a mixed‐method survey soliciting perceptions relative to the organizational strategies and word‐to‐image ratios of two document iterations. Responses ascertained from Likert‐type scales, heat maps, and open‐ended questions suggest that designers, at times, evaluate an information source based on the graphic quality in which it is presented. Taken together, findings from this study might provide some useful guidance for those conveying information to practitioners who are less familiar with academic literature but could benefit from the knowledge provided, thus increasing the likelihood of informed design decision‐making practices. Furthermore, the methods utilized during this inquiry might serve as a pilot for future studies in this area.